Tumor-related denervation pseudohypertrophy of the tongue: A clinical entity in disguise! (Indian Journal of Case Reports, 2018)
Isolated hypoglossal nerve palsy in the base of tongue carcinomas is seldom noticed. The clinical signs are subtle in early stage and can often be overlooked. There may be slight tongue deviation to the affected side, and the tongue feels soft and edematous on careful palpation. There may be associated enlargement of the affected side of the tongue known as “pseudo hypertrophy” due to denervation of its motor supply. Contrast-enhanced magnetic resonance imaging is the gold standard of diagnosis which shows diffuse fatty changes in the affected half of tongue with the preservation of architecture. Clinicians need to be aware of this clinical entity to distinguish it from actual tumor invasion.